Central biogenic amine deficiency with concomitant exploratory behavioral deficits in Dnajc12 knock-out mice - Isaac Bul Deng; Jordan Follett; Jesse D. Fox; Shannon Wall; Matthew J. Farrer (npj Parkinson's Disease)
Abstract Bi-allelic autosomal recessive pathogenic variants in DNAJC12 lead to a constellation of neurological features, including young-onset Parkinson’s disease. DNAJC12 is a co-chaperone for enzymes involved in biogenic amines synthesis. In vitro, we discovered overexpressed DNAJC12 forms a complex with guanine triphosphate cyclohydrolase 1 (GCH1), a rate-limiting enzyme in the synthesis of tetrahydrobiopterin, a cofactor for biogenic amine synthesis. We also confirm DNAJC12’s interaction with tyrosine (TH) and tryptophan hydroxylases, paramount for dopamine (DA) and serotonin (5-HT) synthesis. In-vitro knock-down of DNAJC12 with a siRNA destabilizes DNAJC12-TH-GCH1 complex, whereas reciprocal co-overexpression of TH and GCH1 increases endogenous DNAJC12. Dnajc12 knock-out mice (DKO) exhibit reduced exploratory behavior at 3 months of age in open-field testing. In striatal tissue, total DA and 5-HT, and electrically evoked DA release are all reduced, with enhanced phosphorylation of Th at Ser31 and Ser40. DKO mice present models to develop/refine therapeutics approaches for biogenic amines disorders.